Impact of the input of women’s working hours on household non-economic welfare - Liming Chu; Qi Zhang (BMC Public Health)
Abstract Background The economic functions of families are strengthened by the labor supply of family members. However, an in-depth discussion can still be held on the impact of the labor supply of family members on the non-economic functions of families, such as residential, social and psychological functions. This paper sought to understand the household non-economic welfare of women’s working hours. In addition, the household non-economic welfare effects of women’s working hours in terms of subdividing women’s working hours and fine-tuning household non-economic welfare were explored. The residential, social and psychological effects of women’s working hours were clarified. Method This paper addressed the above problems based on Sen’s welfare theory and Maslow’s hierarchy of needs theory, adopted the feasible ability method, and used nationally representative, timely survey data and data from the 2014–2018 China Family Panel Studies (CFPS). Results In this study, it was shown that the psychological effects of women’s working hours are the largest on average, with an average increase of one hour per week boosting psychological effects by 0.53%. The impact of women’s working hours on both residential and social effects has the extreme points of 68.78 and 35.89 h, respectively. By the interval, the residential effects of women’s working hours are 12.7-16.2% compared with those of weekly working hours shorter than 30 h. Additionally, women’s weekly working hours of more than 60 h have the greatest impact on residential effects, which is 16.2%. From the perspective of gender, the residential effects of women’s working hours are above those of men’s working hours. Compared to weekly working hours of less than 30 h, the social and psychological effects of women’s working hours are weaker than those of men’s working hours. Conclusions This study not only contributes to the understanding of contributions to households from the perspective of labor value but also provides lessons for enhancing household non-economic welfare. Contributions to the literature Limited evidence shows the contributions of working hours and healthy family development in social policies.Women’s working hours increase the residential, social and psychological effects of families. Psychological effects are the largest, with an average increase of one hour per week being associated with an increase of 0.53% in psychological effects. The impact of women’s working hours on subjective health is lower than that of men’s working hours.Few studies systematically analyze the impact of women’s working hours on family residence, socialization and subjective health, and thus target family-friendly policies.